Navigating the mindfield a guide to separating science from pseudoscience in mental health - Lilienfeld, Scott O.; Ruscio, John; Lynn, Steven J. (Prometheus Books, 2008)
Can self-help recordings containing subliminal messages improve your self-esteem or memory? Is hypnotic age-regression therapy a valid way of rediscovering lost childhood memories? Does Thought Field Therapy effectively treat anxiety by manipulating energy fields? A dizzying array of popular psychology books, articles, and promotion campaigns tout these and other alleged remedies for psychological problems. Faced with this confusion, consumers of mental health services need guidelines for finding effective therapy. This useful book brings together accessible, nontechnical articles by leading scientific researchers and clinicians to help answer such critical questions concerning mental health care as: How should I select a therapist? How can I tell the difference between scientifically valid and questionable psychotherapy? Can I trust the diagnosis I have received? If you or someone you know is seeking therapy, this excellent reference book will provide needed guidance for navigating the mental health maze.